Scotland in the age of two revolutions - Adams, Sharon ca. 20./21. Jh. (Studies in early modern cultural, political and social history, 2014)
The seventeenth century was one of the most dramatic periods in Scotland's history, with two political revolutions, intense religious strife culminating in the beginnings of toleration, and the modernisation of the state and its infrastructure. 0This book focuses on the history that the Scots themselves made. Previous conceptualisations of Scotland's "seventeenth century" have tended to define it as falling between 1603 and 1707 - the union of crowns and the union of parliaments. In contrast, this book asks how seventeenth-century Scotland would look if we focused on things that the Scots themselves wanted and chose to do. Here the key organising dates are not 1603 and 1707 but 1638 and 1689: the covenanting revolution and the Glorious Revolution. Within that framework, the book develops several core themes. One is regional and local: the book looks at the Highlands and the Anglo-Scottish Borders. The increasing importance of money in politics and the growing commercialisation of Scottish society is a further theme addressed. Chapters on this theme, like those on the nature of the Scottish Revolution, also discuss central government and illustrate the growth of the state. A third theme is political thought and the world of ideas. The intellectual landscape of seventeenth-century Scotland has often been perceived as less important and less innovative, and such perceptions are explored and in some cases challenged in this volume.00